PROTECTIVE EFFECTS OF AEGLE MARMELOS EXTRACT AGAINEST DOXYRUBICIN INDUCED GENOTOXICITY IN SWISS ALBINO MICE - K. RUDRAMA DEVI,; CH. PRABHAKAR REDDY, (International Journal of Pharma and Bio Sciences, 2014)
In the present study the protective effects of Aegle mamelos fruit extract AMF were carried out in somatic cells of mice against doxyrubicin induced genotoxicity. Three different doses of Aegle Marmelos fruit extract were tested for the antimutagenicity using the micronucleus test in bone marrow cells of mice. The test compound doxyrubicin higher dose 16 mg/kg was injected intrapertioneally prior to the administration of plant extract. The Aegle Marmelos fruit extract did not induce micronuclei significantly by all the three doses tested where as doxyrubicin induced significant increase in the frequency of micronuclei in bone marrow erythrocytes of mice. Pre treatment of mice with AMF for 7 days and simultaneously with a single dose of doxyrubicin, there was a significant inhibition in the percentage of micronuclei was found thus Aegle Marmelos fruit extract modulates the doxyrubicin induced cytotoxicity in a dose dependent way. Thus the overall results suggest the protective nature of Aegle Marmelos fruit extract, it is a safer dietary antioxidant as cancer chemopreventive therapy.